Incomplete excision of basal cell carcinoma (BCC) in the head and neck region: to wait, or not to wait? - Miszczyk, Jakub; Charytonowicz, Michał; Dębski, Tomasz; Noszczyk, Bartłomiej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Recurrence rates for incompletely excised basal cell carcinoma (BCC) vary widely in the literature. Clinical observation is a commonly accepted method of follow up, however such management of these lesions still remains controversial. Aim : To evaluate the rate and factors associated with the recurrence of BCC of the head and neck region after incomplete excision. Material and methods : Medical records of 135 patients with 156 incompletely excised BCCs of the head and neck region were analyzed retrospectively. The primary outcome was the rate of recurrence. Additionally, a correlation of recurrence to clinical and morphological factors was analyzed. Results : Recurrence occurred in 72 (46%) lesions. The mean interval to recurrence was 20 months. In each category of factors, the highest relative risk of recurrence was correlated to: location on the scalp – 2.27, diameter over 2 cm – 1.21, nodular clinical form – 1.29, morpheaform histopathological type – 1.67, recurrent lesion – 1.88, irradicality of excision in the lateral margin – 1.24 and closure of the skin defect with the split-thickness skin graft – 1.42 relative risk. Conclusions : Observation is an acceptable management option as less than a half of incompletely excised BCCs recurred and needed further treatment. As 85% of recurrences occur within 3 years after operation, clinical observation should be particularly careful during this period, however long-term recurrence should not be underestimated.